"I never had the money for blood testing" - Caretakers' experiences of care-seeking for fatal childhood fevers in rural Uganda - a mixed methods study - Kaija Judith; Tomson Göran; Hildenwall Helena; Pariyo George; Peterson Stefan (BMC, 2008)
Abstract Background The main killer diseases of children all manifest as acute febrile illness, yet are curable with timely and adequate management. To avoid a fatal outcome, three essential steps must be completed: caretakers must recognize illness, decide to seek care and reach an appropriate source of care, and then receive appropriate treatment. In a fatal outcome some or all of these steps have failed and it remains to be elucidated to what extent these fatal outcomes are caused by local disease perceptions, inappropriate care-seeking or inadequate resources in the family or health system. This study explores caretakers' experiences of care-seeking for childhood febrile illness with fatal outcome in rural Uganda to elucidate the most influential barriers to adequate care. Methods A mixed methods approach using structured Verbal/Social autopsy interviews and in-depth interviews was employed with 26 caretakers living in Iganga/Mayuge Demographic Surveillance Site who had lost a child 1-59 months old due to acute febrile illness between March and June 2006. In-depth interviews were analysed using content analysis with deductive category application. Results Final categories of barriers to care were: 1) "Illness interpretation barriers" involving children who received delayed or inappropriate care due to caretakers' labelling of the illness, 2) "Barriers to seeking care" with gender roles and household financial constraints hindering adequate care and 3) "Barriers to receiving adequate treatment" revealing discontents with providers and possible deficiencies in quality of care. Resource constraints were identified as the underlying theme for adequate management, both at individual and at health system levels. Conclusion The management of severely ill children in this rural setting has several shortcomings. However, the majority of children were seen by an allopathic health care provider during the final illness. Improvements of basic health care for children suffering from acute febrile illness are likely to contribute to a substantial reduction of fatal outcomes. Health care providers at all levels and private as well as public should receive training, support, equipment and supplies to enable basic health care for children suffering from common illnesses.